Persepsi Konsumen Usaha Bakeri Terhadap Kemasan Plastik dan Green Packaging Berbahan Dasar Kertas - Andani, Wily; Deliana, Yosini; Trimo, Lucyana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Green packaging can be a solution to environmental pollution problems caused by plastic waste generation as a result of bakery business packaging. One of them is paper-based packaging which is considered easier to recycle so that it is also automatically more environmentally friendly. However, bakery businesses still don't use green packaging a lot, which indicates low interest in using green packaging. This study aims to describe consumer perceptions of bakery businesses on plastic packaging and paper packaging. The research was conducted in Indramayu Regency from February to May 2023. The results showed that consumers preferred paper-based packaging to plastic packaging, namely 83.00% for bakery products and 68.00% for sponge cake products. Consumers who like plastic packaging have the perception that plastic packaging for bakery products is practical, attractive, inexpensive, and protects the product better. For sponge cake products, consumers consider plastic packaging to be attractive, practical and protect the product better. Meanwhile, consumers who prefer paper-based packaging think that paper packaging as a packaging for bakery products can reduce plastic waste, is practical, attractive, protects products better, is more hygienic and healthy, and is unique. For sponge cake products, consumers consider paper packaging to be attractive, protect the product better, reduce plastic waste, and be practical. The large number of positive perceptions of paper packaging compared to plastic packaging indicates that consumers have started to switch to environmentally friendly habits.